2024
DOI: 10.1002/anie.202318874
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling pH‐Dependent Adsorption Strength of *CO2 Intermediate over High‐Density Sn Single Atom Catalyst for Acidic CO2‐to‐HCOOH Electroreduction

Bin Sun,
Zaiqi Li,
Difei Xiao
et al.

Abstract: The acidic electrochemical CO2 reduction reaction (CO2RR) for direct formic acid (HCOOH) production holds promise in meeting the carbon‐neutral target, yet its performance is hindered by the competing hydrogen evolution reaction (HER). Understanding the adsorption strength of the key intermediates in acidic electrolyte is indispensable to favor CO2RR over HER. In this work, high‐density Sn single atom catalysts (SACs) were prepared and used as catalyst, to reveal the pH‐dependent adsorption strength and covera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…It has already been reported that the adsorption of metal ions from an aqueous solution is pH-dependent. [59,60] Therefore, the optimum pH was evaluated first. The investigation on the optimum pH for achieving maximum adsorption capacities revealed a peak at pH 6.5, as depicted in Figure S10.…”
Section: Copper Ion Adsorption Studiesmentioning
confidence: 99%
“…It has already been reported that the adsorption of metal ions from an aqueous solution is pH-dependent. [59,60] Therefore, the optimum pH was evaluated first. The investigation on the optimum pH for achieving maximum adsorption capacities revealed a peak at pH 6.5, as depicted in Figure S10.…”
Section: Copper Ion Adsorption Studiesmentioning
confidence: 99%
“…41−44 Meanwhile, the local pH was found to affect the distributions of carbon-based products during eCO 2 RR on the Cu 45,46 electrodes and Sn SACs. 47 Clearly, the selectivity of eCO 2 RR is controlled by multiple factors ranging from the type of metals, electrolytes, pH, and applied potential, 48,49 making it challenging to clarify the role of a single factor unambiguously. In this work, we are striving to illustrate the metal-dependent selectivity of two-electron eCO 2 RR at different potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the influences of electrolytes on the adsorption and reduction of CO 2 have been widely investigated in both experiments and simulations, where the types and compositions of cations and anions played diverse roles in CO 2 reduction. Meanwhile, the local pH was found to affect the distributions of carbon-based products during eCO 2 RR on the Cu , electrodes and Sn SACs . Clearly, the selectivity of eCO 2 RR is controlled by multiple factors ranging from the type of metals, electrolytes, pH, and applied potential, , making it challenging to clarify the role of a single factor unambiguously.…”
Section: Introductionmentioning
confidence: 99%
“…Converting CO 2 into value-added chemicals or fuels is an appealing method for reducing CO 2 emissions and thereby achieving carbon neutrality. Nevertheless, the inertness and thermodynamic stability of CO 2 severely constrain its conversion efficiency. Electroreduction CO 2 (CO 2 RR) has attracted substantial attention from researchers due to its high conversion efficiency, mild reaction conditions, and elevated energy efficiency. The specific products formed depend on the number of protons, electrons, and reduction pathways involved, as the CO 2 RR is a multiproton-coupled and multielectron-transfer processes. , By altering the catalytic conditions or reduction pathways, different surface-bound species can generate corresponding reaction intermediates, leading to the formation of different carbon-containing products such as carbon monoxide (CO), formic acid (HCOOH), methane (CH 4 ), and so on. HCOOH, revered as a high-value CO 2 electroreduction product, is an important raw material in the pharmaceutical and chemical industries, making it one of the most economically viable products in the CO 2 RR process. In the electrochemical reaction mechanism, HCOOH requires minimal electron transfer during the electroreduction process, which not only simplifies the reduction of CO 2 to HCOOH but also allows for its subsequent conversion into other raw materials such as hydrogen (H 2 ), CO, and methanol (CH 3 OH) through simple catalytic reactions to meet various industrial production needs. Therefore, the rational design of catalysts and reduction pathways is crucial to the selectivity and yield of the products.…”
Section: Introductionmentioning
confidence: 99%